2011
DOI: 10.1165/rcmb.2010-0052oc
|View full text |Cite
|
Sign up to set email alerts
|

The Mevalonate Cascade as a Target to Suppress Extracellular Matrix Synthesis by Human Airway Smooth Muscle

Abstract: Smooth muscle cells promote fibroproliferative airway remodeling in asthma, and transforming growth factor β1 (TGFβ1) is a key inductive signal. Statins are widely used to treat hyperlipidemia. Growing evidence indicates they also exert a positive impact on lung health, but the underlying mechanisms are unclear. We assessed the effects of 3-hydroxy-3-methlyglutaryl-coenzyme A (HMG-CoA) reductase inhibition with simvastatin on the fibrotic function of primary cultured human airway smooth muscle cells. Simvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
3
51
0
1
Order By: Relevance
“…These findings suggest that statins, other than being effective in preventing prenylation-mediated AHR induced by LPS, may also play a pivotal role in the regulation of airway smooth muscle tone by triggering nitric oxide synthesis (57). Our results are in agreement with recent clinical findings that demonstrated a protective role of statins in patients suffering with asthma (58)(59)(60).…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that statins, other than being effective in preventing prenylation-mediated AHR induced by LPS, may also play a pivotal role in the regulation of airway smooth muscle tone by triggering nitric oxide synthesis (57). Our results are in agreement with recent clinical findings that demonstrated a protective role of statins in patients suffering with asthma (58)(59)(60).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies revealed that statins reduce RhoA activation by suppressing the mevalonate cascade and this inhibitory effect is related to geranylgeranylpyrophosphate (GGPP) but not farnesylpyrophosphate (FPP), which lie downstream of mevalonate. Schaafsma et al showed that simvastatin suppresses expression of extracellular matrix components such as collagen I and fibronectin, which are induced by TGF-b1 in ASM cells [26]. They also reported that PDGF induced RhoA activation and ASM cell proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites of the MA pathway, particularly the isoprenoids, have been associated with processes linked to asthma and respiratory ailments, including allergic eosinophilic inflammation [31,36,69], Rho GTPase signaling in airway smooth muscle cells and airway hyperreactivity (AHR) [48,70,71], adaptive immunity and type 2 inflammation [72,73], airway smooth muscle cell proliferation [43], and mucus production [74] (Figure 2). Since these pathogenic mechanisms occur in asthma, perturbation of the MA pathway likely affects disease pathogenesis [29,70].…”
Section: The Mevalonate Pathway Statins and Relevance To Asthmamentioning
confidence: 99%